Geometric influence of entry angle and contraction ratio on droplet regime transition from trap to squeeze in microchannel - Hoang, Van Thanh; Nguyen, Thanh Tung; Pham, Hong Vinh (Vietnam Journal of Mechanics, 2025)
To precisely control and manipulate the main droplet within a microfluidic system, aside from modifying the flow characteristics and liquid properties, the geometric design of the microchannel also plays a crucial role in the droplet dynamics. Three main regimes are observed in a droplet in a contraction microchannel: trap, squeeze, and breakup. This study employs theoretical and three-dimensional numerical models to assess how two geometric parameters of the microchannel, namely the entry angle (α) and the contraction ratio (C), influence the critical capillary number (Ca) for droplet dynamics of trap-squeeze regime transition. The model's predictions align perfectly with simulation results. Additionally, the study investigates the impact of the entry angle on droplet deformation.